ПРИМЕНЕНИЕ ФЕРМЕНТНОГО ПРЕПАРАТА ПЕРОКСИДАЗЫ ГРИБА PLEUROTUS OSTREATUS УЗБИ-И105 В БИОХИМИЧЕСКОЙ ПРАКТИКЕ (Experimental biology, 2015)
Laboratory regulations, cheap economic scheme and technical and economic calculations have been worked out, offered and conducted. The obtained peroxidase was used us a marker in conducting of immuno-enzyme analyses for obtaining of conjugates against diphtheria toxin and in test-systems identification of AIDS viruses instead of widelyused commercial peroxidase were isolated from horseredish. Peroxidase is supposed to be used in medical diagnostics in immuno-enzyme analyses in food industry for detoxycation of phenolic compounds in the conditions of laboratory biochemical practice.
Keywords: biochemical practice; AIDS viruses